Eu(II)-Activated Silicates for UV Light-Emitting Diodes Tuning into Warm White Light - Bispo-Jr, Airton G. [UNESP]; Lima, Sergio A. M. [UNESP]; Carlos, Luís D.; Pires, Ana M. [UNESP]; Ferreira, Rute A. S. (Wiley, 2020)
White-light-emitting diodes (WLEDs) are the main white light source for general lighting due to high-luminous efficacy (>150 lm W−1), long lifespan (5 × 104 h), and environmentally friendly properties. Despite the current maturity and reliability of the solid state-lighting field, the control of the correlated color temperature (CCT) tuning is still a challenge, arising from the lack of red emission color in the current design of commercial WLEDs. Moreover, as this aspect is often associated with dysregulations of the human circadian rhythm, the need for novel WLEDs is of enlarged societal relevance. In this scope, herein, warm WLED prototypes are fabricated by coating near-UV-emitting LEDs with a mixture of the yellow-emitting polyphasic Sr2SiO4:Eu(II) (S2S) and the blue-emitting BaMgAl10O17:Eu(II) (BAM) phosphors dispersed in poly(methyl methacrylate). As the amount of S2S increases in the phosphor mixture, the CCT values of the WLEDs decrease from 6500 K (ideal for daylight application) to 4000 K (ideal for night light application), with a luminous efficacy of radiation of 404 lm W−1, among the best figures of merit for WLEDs. Furthermore, all the WLED devices also display a desirable color rendering index (CRI > 75), comparable with the commercial WLED, independent on the operating voltage.
Keywords: new-UV LEDs; phosphors; solid-state lighting; warm white light